Life-Events Mediate the Prediction of Parental Alienation on Depression in Rural Left-Behind Children: A Longitudinal Study - Qin, Xuemei; Sun, Xiaoxiao; Zhang, Mengjia; Chen, Beijing; Xie, Fei; Chen, Zhaohua; Shen, Sitong; Wen, Chong; Ren, Xiaomei; Dai, Qin (Frontiers in Psychiatry, 2022)
Objectives: Long-time separation with parents during early life such as left-behind children (LBC, one or both of whose parents are leaving for work for at least 6 months) may contribute to high alienation towards parents and endanger their mental health (e.g. depression). However, the dynamic status of depression and potential prediction of alienation on depression in LBC remained largely unknown. This study aimed to examine the dynamic status of depression, prediction of alienation towards parents on later depression in rural LBC, and a potential mediation of life-events. Methods: 877 LBC in rural areas of China were recruited and surveyed at five time-points (baseline T0, 1-month T1, 3-month T2, 6-month T3, 12-month T4) with the IAP, CDI, and ASLEC. The Hierarchical Linear Model (HLM) and Hayes’s PROCESS macro model was conducted to estimate the developmental trend and hierarchical predictors of depression. Results: LBC aged 9 years old experienced higher depression than children with other ages. At baseline, children in the family atmosphere of frequent quarrels and compulsive parenting style reported a higher level of alienation towards parents, life-events, and depression. Alienation towards parents, life-events, and depression were positively and moderately correlated with each other (r = 0.14~0.64). The HLM model depicted a linear decline in depression, alienation, and life-events with an average rate of 0.23, 0.24, and 0.86 respectively during the five-time points. T0 alienation towards parents and T0 life-events positively predicted the developmental trajectory of depression over time, and T0 life-events positively predicted the descendant rate of depression. Notably, life-events mediated the prediction of baseline alienation towards parents on T4 depression in LBC. Conclusions: The current study is among the first to reveal that alienation towards parents predicts the developmental trajectory of later depression in LBC. The findings that life-events mediate the prediction of alienation on later depression further suggest the importance of family and social factor in the occurrence of depression in LBC. The findings warrant the necessity to consider the family and social factors when evaluating and reducing risks for mental health problems of LBC, i.e., relationship with parents (especially alienation towards parents) and life-events need further attention.